5-aza-2'-deoxycytidine Inhibits the Proliferation of Lung Fibroblasts in Neonatal Rats Exposed to Hyperoxia - Shimeng Zhao; Meiling Cao; Hongmin Wu; Yu Hu; Xindong Xue (Elsevier, 2017)
A persistent increase in the number of lung fibroblasts (LFs) is found in the interstitium of the lungs of infants with bronchopulmonary dysplasia (BPD), which leads to lung fibrosis. P16 methylation plays an important role in the pathogenesis of BPD. 5-aza-2'-deoxycytidine (5-aza-CdR) is a major methyltransferase-specific inhibitor. This study investigated the effects of 5-aza-CdR on LFs in vitro from a hyperoxia-induced lung fibrosis model in newborn rats. Methods: Methylation-specific polymerase chain reaction (PCR) and Western blotting were performed to determine P16 gene methylation status and protein expression after LFs were treated with 0 μmol/L, 0.5 μmol/L, 1.0 μmol/L, and 5.0 μmol/L 5-aza-CdR for 120 hours. Proliferation was assessed by an MTT assay after LFs were treated with 0 μmol/L, 0.5 μmol/L, 1.0 μmol/L, and 5.0 μmol/L 5-aza-CdR for 24 hours, 48 hours, 72 hours, 96 hours, and 120 hours. At the final time point, cells were also analyzed by flow cytometry to identify any change in their cell cycle profiles. Results: A methylated P16 gene promoter was detected in hyperoxia LFs. Following treatment with 5-aza-CdR, partial methylation and demethylation was detected. The expression protein's level of the P16 gene was significantly higher in the 5.0 μmol/L 5-aza-CdR-treated group compared with that in the control group (p < 0.01). The cell growth rate at each tested time point was lower in the 5-aza-CdR-treated group compared with that in the control group after 72 hours (p < 0.01). Flow cytometry revealed that the cells in the 1.0 μmol/L and 5.0 μmol/L 5-aza-CdR-treated groups were apparently arrested in the G0/G1 phase and that the number of cells in the S phase was significantly lower than the control group (p < 0.01). Conclusion: 5-aza-CdR inhibits the growth of the LFs in hyperoxia-induced neonatal BPD rats in vitro by demethylating the P16 gene.